Biological Profiling Enables Rapid Mechanistic Classification of Phenotypic Screening Hits and Identification of KatG Activation-Dependent Pyridine Carboxamide Prodrugs With Activity Against Mycobacterium tuberculosis - Chengalroyen, Melissa D.; Jordaan, Audrey; Seldon, Ronnett; Ioerger, Thomas; Franzblau, Scott G.; Nasr, Mohamed; Warner, Digby F.; Mizrahi, Valerie (Frontiers in Cellular and Infection Microbiology, 2020)
Compounds with novel modes of action are urgently needed to develop effective combination therapies for the treatment of tuberculosis. In this study, a series of compounds was evaluated for activity against replicating Mycobacterium tuberculosis and Vero cell line toxicity. Fourteen of the compounds with in vitro activities in the low µM range and a favorable selectivity index were classified using reporter strains of M. tuberculosis which showed that six interfered with cell wall metabolism and one disrupted DNA metabolism. Counter-screening against strains carrying mutations in promiscuous drug targets argued against DprE1 and MmpL3 as hits of any of the cell wall actives and eliminated the cytochrome bc1 complex as a target of any of the compounds. Instead, whole-genome sequencing of spontaneous resistant mutants and/or counter-screening against common isoniazid-resistant mutants of M. tuberculosis revealed that four of the six cell wall-active compounds, all pyridine carboxamide analogues, were metabolized by KatG to form InhA inhibitors. Resistance to two of these compounds was associated with mutations in katG that did not confer cross-resistance to isoniazid. Of the remaining seven compounds, low-level resistance to one was associated with an inactivating mutation in Rv0678, the regulator of the MmpS5-MmpL5 system, which has been implicated in non-specific efflux of multiple chemotypes. Another mapped to the mycothiol-dependent reductase, Rv2466c, suggesting a prodrug mechanism of action in that case. The inability to isolate spontaneous resistant mutants to the seven remaining compounds suggests that they act via mechanisms which have yet to be elucidated.